2018
DOI: 10.1002/bjs.10712
|View full text |Cite
|
Sign up to set email alerts
|

[18F]Fluorodeoxyglucose PET/CT and prediction of histopathological response to neoadjuvant chemotherapy for adenocarcinoma of the oesophagus and oesophagogastric junction

Abstract: FDG-PET/CT after the first cycle of chemotherapy does not predict histopathological response in patients with adenocarcinoma of the oesophagus and oesophagogastric junction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…All patients had gastro‐oesophageal adenocarcinoma. Three studies 27,28,30 used neo‐adjuvant chemotherapy alone prior to surgery, one 29 used neo‐adjuvant chemoradiotherapy and two 14,31 used initial neo‐adjuvant chemotherapy followed by radiotherapy in metabolic non‐responders (Table 2). In total, 20/519 (3.9%) of patients progressed during neo‐adjuvant therapy and were no longer eligible for surgery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients had gastro‐oesophageal adenocarcinoma. Three studies 27,28,30 used neo‐adjuvant chemotherapy alone prior to surgery, one 29 used neo‐adjuvant chemoradiotherapy and two 14,31 used initial neo‐adjuvant chemotherapy followed by radiotherapy in metabolic non‐responders (Table 2). In total, 20/519 (3.9%) of patients progressed during neo‐adjuvant therapy and were no longer eligible for surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Both reviewers identified 25 of the 32 full-text articles (78.1%) and the remaining 7 were included after agreement by the third reviewer. Important characteristics of the included studies 14,[27][28][29][30][31] are detailed in Table 1.…”
Section: Re Sultsmentioning
confidence: 99%
“… 7 In the consecutive MUNICON I and II studies, the same group of investigators demonstrated that an early metabolic response-guided treatment algorithm identifies non-responding patients and allows for the adjustment of the perioperative treatment strategy. 8 , 9 Since then, several other groups developed response-guided treatment algorithms with some modifications in methodology, endpoints and trial designs 10 13 but implementation into clinical practice is still lagging behind.…”
Section: Introductionmentioning
confidence: 99%